Chilling requirement for dormancy bud break in European Pear - Brighenti L.M.* (2011)
Pear trees require periods of low temperatures (4 to 10°C) during autumn and winter to start a new growth season, otherwise the tree will keep under dormancy or will present an irregular shooting and blooming. The objective for this work was to identify the chilling requirement to overcome dormancy and rate of sprouting buds of European pear (Pyrus communis L.) kept at chilling conditions for different periods. The experiment was carried out using the single node cuttings test with buds of twigs from the previous growth season and placed in controlled cold conditions. Cultivars 'Forelle', 'Packham's Triumph', 'Winter Bartlett', 'Red Bartlett', 'Max Red Bartlett' and 'Rocha' were subjected to seven different treatments: 0, 300, 450, 600, 750, 900 and 1050 hours at cold temperatures of 3±1°C. The variables evaluated were percentage of bud break and period of time to reach that phase. We evaluated the bud sprouting, considering the green tip stage. From these data, we calculated the average time of sprouting (BMR) and the percentage of shoot buds in each treatment. Cultivars 'Winter Bartlett' and 'Red Bartlett' did not reach the maximum percentage of sprouting in any treatment of cold applied. The percentage of shoot buds was also larger when the twigs were exposed to 1050 cold units in any cultivar.